2006
DOI: 10.1007/s00262-006-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

STEAP, a prostate tumor antigen, is a target of human CD8+ T cells

Abstract: STEAP is a recently identified protein shown to be particularly overexpressed in prostate cancer and also present in numerous human cancer cell lines from prostate, pancreas, colon, breast, testicular, cervical, bladder and ovarian carcinoma, acute lymphocytic leukemia and Ewing sarcoma. This expression profile renders STEAP an appealing candidate for broad cancer immunotherapy. In order to investigate if STEAP is a tumor antigen that can be targeted by specific CD8(+) T cells, we identified two high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 25 publications
1
55
0
1
Order By: Relevance
“…STEAP1 peptides have been recently demonstrated to induce antigen-specific CTLs that were able to recognize and destroy STEAP1-expressing tumor cells in vitro [2,5]. Active immunization against STEAP1 using DNA prime/modified vaccinia virus Ankara boost strategy inhibits prostate cancer progression in a murine model [6].…”
Section: Normalized Steap1 Protein Expression Was Significantly Corrementioning
confidence: 99%
See 1 more Smart Citation
“…STEAP1 peptides have been recently demonstrated to induce antigen-specific CTLs that were able to recognize and destroy STEAP1-expressing tumor cells in vitro [2,5]. Active immunization against STEAP1 using DNA prime/modified vaccinia virus Ankara boost strategy inhibits prostate cancer progression in a murine model [6].…”
Section: Normalized Steap1 Protein Expression Was Significantly Corrementioning
confidence: 99%
“…Given its increased expression in cancer tissues, STEAP1 could be a promising target for T-cell based or antibody immunotherapy. In prostate cancers, STEAP1-specific cytotoxic T lymphocytes (CTLs) were found to inhibit the growth of transplantable prostate tumor cells in murine models [2,4,5]. An immunization with recombinant DNA or modified vaccinia virus Ankara vector delivering STEAP1 antigen inhibited prostate cancer progression in a murine subcutaneous syngeneic tumor model [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both can be found in human and mouse, but with slightly different constitutions; human STEAP [86][87][88][89][90][91][92][93][94] differs at position 9 from the mouse peptide (FLYTLLREV!-FLYTLLREI) and human STEAP 262-270 differs at position 6 from the mouse peptide (LLLGTIHAL!LLLGTVHAL). The latter has been initially identified as a TAA of STEAP3 (76,77). Despite the differences mentioned, both STEAP [86][87][88][89][90][91][92][93][94] and STEAP 262-270 peptides are immunogenic in vivo, in HLA-A Ã 0201 transgenic mice (HHD), and in vitro, in peptide-specific human CD8 þ T cells from healthy donors.…”
Section: Steap Proteins As Immunotherapeutic Targetsmentioning
confidence: 99%
“…This guarantees the sole expression of the HHD molecule on the cell surface, making sure that any identified CTL epitopes are HLA-A2 restricted [98]. HHD mice allow epitopes which are presented on human HLA-A2 to be examined for their ability to induce T cell responses in a variety of studies; for example STEAP, a prostate tumour antigen has been shown to be targeted by anti-tumour T cells [99] and DNA vaccines encoding Wilms tumour antigen 1 induce cytotoxic responses in mice [100] using this model system.…”
Section: Genetically Modified Micementioning
confidence: 99%